Comparative analysis of hierarchical cluster protocols for wireless sensor networks. (15th April 2019) - Gherbi, Chirihane; Aliouat, Zibouda; Benmohammed, Mohamed
Wireless sensor networks (WSNs) give minimum expenses answers for different true issues. WSN is made of independent sensors built over a distance to control physical or environmental conditions, for example, sound, vibration, weight, temperature, movement or toxins, and to accurately exchange their information through the network to a main area. WSNs are deployed in hostile environments so the network becomes highly vulnerable to the risk of attack. Therefore, numerous directing, power administration and information spread protocols have been particularly intended for WSNs. Planning a power proficient directing mechanism to expand the whole network lifetime has turned out to be essential. In this paper, performances of different routing protocols are compared and the diverse various hierarchical directing protocols are discussed.